Direct Synthesis of Peptide‐Containing Silicones: A New Way to Bioactive Materials. Issue 56 (11th September 2020) - Martin, Julie; Wehbi, Mohammad; Echalier, Cécile; Hunger, Sylvie; Bethry, Audrey; Garric, Xavier; Pinese, Coline; Martinez, Jean; Vezenkov, Lubomir; Subra, Gilles; Mehdi, Ahmad
Abstract: A simple and efficient way to synthesize peptide‐containing silicone materials is described. Silicone oils containing a chosen ratio of bioactive peptide sequences were prepared by acid‐catalyzed copolymerization of dichlorodimethylsilane, hybrid dichloromethyl peptidosilane, and Si(vinyl)‐ or SiH‐functionalized monomers. Functionalized silicone oils were first obtained and then, after hydrosilylation cross‐linking, bioactive polydimethylsiloxane (PDMS)‐based materials were straightforwardly obtained. The introduction of an antibacterial peptide yielded PDMS materials showing activity against Staphylococcus aureus . PDMS containing RGD ligands showed improved cell‐adhesion properties. This generic method was fully compatible with the stability of peptides and thus opened the way to the synthesis of a wide range of biologically active silicones. Abstract : Simple and efficient synthesis of peptide‐containing silicone materials is described. Antibacterial peptide‐functionalized silicone oils were prepared and then cross‐linked by hydrosilylation to afford active polydimethylsiloxane (PDMS) materials in a single step. This generic method can be applied to any peptide sequence and thus opens the way to the synthesis of a wide range of biologically active silicones.